Transience of the body, performativity of psychosocial landscapes and subjectivations on the surface of the skin: lines of force of a body in a state of performance - Alves, Lindomberto Ferreira (Revista do Colóquio, 2024)
This article explores three lines of poetic force present in the work of artist Rubiane Maia: the transience of the body, the performativity of psychosocial landscapes and subjectivations on the surface of the skin. Through a theoretical exercise, different concepts are related to highlight these forces in her performances. The works “Skin. Surface. Market” (2006), “Wedding Rehearsal” (Vermelho-Mulher) (2011) and “O Jardim” (The Garden) (2015) are analyzed as case studies, elucidating such reflections. It is argued that these lines converge to consolidate performance as a space for the creation of new ways of being and existing in the world.